2003
DOI: 10.1074/jbc.m301903200
|View full text |Cite
|
Sign up to set email alerts
|

Type III Protein Translocase

Abstract: Type III protein secretion (TTS) is catalyzed by translocases that span both membranes of Gram-negative bacteria. A hydrophilic TTS component homologous to F 1 /V 1 -ATPases is ubiquitous and essential for secretion. We show that hrcN encodes the putative TTS ATPase of Pseudomonas syringae pathovar phaseolicola and that HrcN is a peripheral protein that assembles in clusters at the membrane. A decahistidinyl HrcN derivative was overexpressed in Escherichia coli and purified to homogeneity in a folded state. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Mutation of active site residues in the C-terminal domain of FliI are dominant negative for swarming motility (16 -18). Similar studies on the homologous InvC type III ATPase also demonstrated negative dominance of catalytic site mutations that were relieved on disruption of membrane localization of the ATPase (20,21).…”
mentioning
confidence: 62%
“…Mutation of active site residues in the C-terminal domain of FliI are dominant negative for swarming motility (16 -18). Similar studies on the homologous InvC type III ATPase also demonstrated negative dominance of catalytic site mutations that were relieved on disruption of membrane localization of the ATPase (20,21).…”
mentioning
confidence: 62%
“…The specific activity increases with an increase in the enzyme concentration until a maximal activity of 50 nmol/ min/mg. Concentration-dependent activity is suggestive of cooperative association and has been identified for a number of characterized NTPases, including AAA-ATPases (34).…”
Section: Resultsmentioning
confidence: 99%
“…4), appears to be an integral membrane protein. To further characterize CtsP and CtsX as integral or peripheral membrane proteins, we analyzed the avidity of their association with C. jejuni membranes by employing different extraction procedures commonly used to release peripherally associated membrane proteins (43).…”
Section: The Walker Boxes Of Ctse and Ctsp Are Required For Function mentioning
confidence: 99%